Multiple sustained arrhythmias after STEMI: Case report (Research, Society and Development, 2025)
Cardiac arrhythmias are the most common complication following acute myocardial infarction (AMI), particularly in cases with ST-segment elevation (STEMI). Although usually self-limited, sustained arrhythmias are associated with worse prognosis and higher in-hospital mortality. Objective: To report a case of multiple sustained arrhythmias — both ventricular and supraventricular — occurring late after STEMI. Methods: Case report of a 64-year-old male admitted with anteroseptal STEMI, who underwent primary percutaneous coronary intervention (PCI). Results: The patient developed sustained ventricular tachycardia, ventricular fibrillation, and paroxysmal supraventricular tachycardia refractory to conventional therapy, associated with QT interval prolongation. After bicameral pacemaker implantation, QT interval shortening and complete arrhythmic resolution were observed, leading to progressive clinical recovery and hospital discharge. Conclusion: Sustained post-infarction arrhythmias, although uncommon, require prompt recognition and intensive management due to their association with early mortality. The coexistence of ventricular and supraventricular arrhythmias underscores the need for continuous electrocardiographic monitoring and multidisciplinary care, especially in patients with left ventricular dysfunction and QT prolongation.